Giving thanks : poems, prayers, and praise songs of thanksgiving - Paterson, Katherine; Dalton, Pamela (Illustrator) (Handprint Books, 2013)
Meditations on what it means to be truly grateful are paired with meticulous and exquisite cut-paper illustrations to give you a collection of more than 50 graces, poems and praise songs harvested from a wide range of cultures, religions, and voices.